Resonance suppression strategy of DC distribution system based on reduced-order hybrid control algorithm - Zheng, Zonghua; Wu, Xudong; Zheng, Feng; Liu, Baojin; Liang, Ning (Frontiers in Energy Research, 2023)
As a complex dynamically strongly coupleddynamic strong coupling system, DC distribution system often suffers from voltage collapse owing due to system resonance. In order to suppress distribution network resonance and bus voltage fluctuation, this paper proposes a hybrid control algorithm to suppress DC distribution system resonance to further enhance DC system stability. In this paper, the output voltage of the line regulation converter (LRC) is the target of the study. A current prediction model is introduced in the inner loop of the converter control, which can enhance the dynamic responsiveness of the system and eliminate the PWM modulator and parameter tuning, achieving achieve the unitization of the inner loop of the current. By constructing the inverse model of the controlled object, the outer voltage loop is unitized under the control of two-degrees -of-freedom. The hybrid control enables the bus voltage to follow the reference voltage exactly, which suppresses resonance peaks in the voltage transfer function and reduces bus voltage fluctuations. Finally, the proposed hybrid control algorithm is simulated and verified in MATLAB/Simulink platform. The results show that the control strategy can effectively suppress the resonance and bus voltage fluctuation of the DC distribution system and enhance the dynamic characteristics and anti-interference capability of the distribution network.